2003
DOI: 10.1097/00004032-200304000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Parameter Uncertainties Within the Icrp-66 Respiratory Tract Model: Particle Clearance

Abstract: Quantifying radiological risk following the inhalation of radioactive aerosols entails not only an assessment of particle deposition within respiratory tract regions but a full accounting of clearance mechanisms whereby particles may be translocated to adjacent respiratory tissue regions, absorbed to blood, or released to the gastrointestinal tract. The model outlined in ICRP Publication 66 represents to date one of the most complete overall descriptions of particle deposition and clearance, as well as localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
0
24
0
3
Order By: Relevance
“…Consequently, evaluating the chemical characteristics of these ultrafine nanoparticles is particularly important for an understanding of the impact to general health of airborne particulates that are small enough to enter the human respiratory system. Because a large proportion of nanoparticles penetrate the lung periphery, i.e., the alveolar region, particles deposited in the alveoli are readily transferred to the blood and are then quickly dispersed throughout the human body, including infants (Hinds, 1999;Bolch et al, 2001;Semmler-Behnke et al, 2012). Furthermore, at least one report on the effect that oral exposure to nanoparticles has on the human body, has determined that all kind of nanoparticle behavior in the environment could be issues that should be investigated (Mahler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, evaluating the chemical characteristics of these ultrafine nanoparticles is particularly important for an understanding of the impact to general health of airborne particulates that are small enough to enter the human respiratory system. Because a large proportion of nanoparticles penetrate the lung periphery, i.e., the alveolar region, particles deposited in the alveoli are readily transferred to the blood and are then quickly dispersed throughout the human body, including infants (Hinds, 1999;Bolch et al, 2001;Semmler-Behnke et al, 2012). Furthermore, at least one report on the effect that oral exposure to nanoparticles has on the human body, has determined that all kind of nanoparticle behavior in the environment could be issues that should be investigated (Mahler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…UFPs are efficiently deposited in the human airway (Wilson et al, 1985;Jaques and Kim, 2000;Kim and Jaques, 2005), with the majority of 20-100 nm particles depositing in the respiratory bronchioles and alveoli (Bolch et al, 2001;Lazardis et al, 2001). People with asthma or chronic obstructive pulmonary disease may be particularly susceptible to the respiratory effects of UFPs, as deposition is greater in these individuals (Brown et al, 2002;Chalupa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The U S ratios between our and DCAL results are in the range of 0.995-1.001. Bolch et al (2001Bolch et al ( , 2003 analyzed the influences of uncertainties of particle deposition and clearance parameters on the nuclear transformations in the ICRP HRTM. It is found that in all the regions of the respiratory tract for an adult male at light exertion, uncertainties in particle deposition fractions are distributed only over a range of about a factor of 2-4 for particle sizes between 0.005 and 0.2 mm.…”
Section: Quality Assurance and Uncertainty Of Dose Coefficientmentioning
confidence: 99%